ATIVIDADES INVESTIGATIVAS PARA O ENSINO DE MATEMÁTICA PARA ALUNOS DE 5º SÉRIE DO ENSINO FUNDAMENTAL - Brum, Maria Gorete Nascimento (2012)
The present research investigated the contributions of the use of investigative activities in the exploration of standards and regularities in numerical and geometric sequences as elements that become easy the learning of the pupils of 5º series of Basic Education. This work was carried through with a group of 5º degree with 30 pupils of the State school of Basic Education Marechal Rondon in the periphery of the city of Santa Maria, RS. The date of the research, qualitative matrix, had been gotten of the direct action teacher s in the classroom with the pupils by means of the observation and the registers in its diary beyond the analysis of the pupils, work and the presentations to the great group. It can be inferred that the objectives considered in the sessions as explore the standard concept, to recognize, to describe standards, to continue the drawing of the sequence was reached. The objectives to generalize, to explore the notion and properties of the numbers pairs, uneven and multiple, as well as the involution of natural numbers and to work the concept of area and perimeter of plain figures, partially had been reached. The results presented for the pupils it can be concluded that the investigative activities worked with the pupils of 5ª degree, had propitiated the increase of interest, the motivation in the accomplishment of the activities proposals in classroom and as consequence had an improvement in the learning.